تقييم تأثير وسائل الاعلام والدعاية على إدراک المستخدمين للعمارة والعمران "دراسة حالة مشروعات الاسکان في مصر" - محمود سليمان; ولاء زقدان (Journal of Engineering Research - Egypt)
يعتبر الإعلام أحد روافد الثقافة والفنون والعلوم في المجتمعات الإنسانية عامة، يندرج في ذلک علکوم وفنکون العمکارل والعمکران التکي أوکيد مکنوأ ومسک أفکراهذه المجتمعات، لذل فإن وسائل الإعلام بننواعها المختلفة وما أبثه م مکوا ورسکائل لاعلاميکه ي کون لهکا أکن ير ربيکر فکي أوک يل قافکة وف کر أفکرا هکذه المجتمعکاتومعتقداأهم، رذل أوجيه سلورهم ورغباأهم. على لان علوم وفنون العمارل والعمران لا أحظى غالبکا بنصکي رکافي مک التنکاو فکي الوسکائل الإعلاميکة رنحکد القضکاياالثقافية والمعرفية الهامة مقارنة بالعديد م المجالات الثقافيکة اأخکرأ، ومک کم يفتقکد أفکرا المجتمک لالکى الإ راع الکواعي وال کافي لحقيقکة ماهيکة العمکارل والعمکرانومجالاأه المختلفة خاصة مجا الإس ان. وحيث أن مفهوم الإس ان، الذي يعد أحد أهم مقومات العمران و العمارل، هو أهم وأشمل مما هو متعکار عليکه فکي وسکائلالإعلام، ومتداو له بي عموم أفرا المجتم ، م حيث أن رؤية اأعلام للإس ان لا أتجاوز رون أن الموروعات الس نية هي أصکاميم هندسکية نکم موکروعاتاسککتثمارية ذات أهککدا ربحيککة بالمقککام الاو ، و أنهککا لککم أعککد أتوافکک رثيککرا مکک الاحتياجککات اأساسککية للمسککتخدمي مکک حيککث المسککاحات الو يفيککة، أو الاحتياجککاتالاجتماعية، أو الاحتياجات البيئية، وف قافة المجتم وخصائصهم المميزل، لذا فنن هذا البحث يختص بنلقکا الضکو علکى الکدور الکذي أقکوم بکه وسکائل الاعکلام فکيالتن ير على قافة المجتم ووعيکه ولا رارکه لماهيکة العمکارل و العمکران، وانع اسکات ألک الثقافکة المصکاغة مک ابکل وسکائل الإعکلام علکى العمکارل و العمکران و البيئکةالموکيدل عامکة، و علکى الاسک ان خاصکة، مک أجکل الوصکو لالکى أحقيک علااکات أن يريکه لايجابيکه بکي وسکائل الإعکلام و مفکاهيم المجتمک للعمکارل والعمکران عامکة ،والإس ان خاصة.ويهد البحث بو ل رئيسي لالى رف مستوأ الوعي والإ راع عند أفکرا المجتمک بمفکاهيم وأسک العمکارل والعمکران عامکه والإسک ان خاصکة، والارأقکا بکوعيأفکرا المجتمک مک البکاحثي عک الإسک ان أجاههمکا أکدريجيا مک خکلا وسکائل الإعکلام المختلفکة بمکا يحقک أعظکيم ادراأکه علکى الاختيکار الصکحي وألبيکة احتياجاأکهومتطلباأه الاساسية، حيث أمحورت أهدا البحث فيما يلي:− أوني مدأ أن ير وسائل الإعلام على أعريف ماهية ومفاهيم العمارل والعمران عامة، والإس ان خاصة.− أقييم ور الوسائل الاعلامية م حيث الايجابية أو السلبية بتحليل نماذج م الرسائل الإعلامية والإعلانية التي أ کون غالبکا بتکن ير مک رؤيکة المطکوريالمستثمري في أطار سعيه لتسوي منتجاأهم الس نية.− رصد المعايير التي أرأ ز عليها هذه الوسائل الإعلامية في أسويقها للمنتج المعماري م حيث رونها أمينه في طري عرنها لخصکائص المنکتج بحيکثيتحق للمستخدم المعرفة الحقيقة لما يقوم بإاتنائه.− ونک منظومکة نکوابل لضکبل أسکالي التکرويج والتسکوي فکي الإعکلام فيمکا يخکتص بالمعلومکات التکي يجک أقکديمها بوسکائل الإعکلام حکو المنتجکاتالمعمارية في سوق الإس ان، بحيث ي ون للباحثي ع الإس ان القدرل فکي أحديکد اأنسک لهکم، ممکا هکو معکرو مک نمکاذج سک نية، وفک خصائصکهمواحتياجاأهم المتعد ل والمتنوعة.Abstract:Media is considered one of the branches of culture, arts, and sciences within the human communities in general. This includes the arts and sciences of architecture andsettlement, which are concerned with erecting and constructing the residence and houses of the members of such communities. Thus, all different types of mass media andtheir relevant broadcasted materials and conveyed messages, have such a great influence on shaping the culture, mentality, and beliefs of such human communities, inaddition to their influential impact on the orientation of their behavior. Yet, the mass media does not tackle the science and art of architecture and ekistics – where theyrepresent one of the most important cultural and cognitive issues- sufficiently, if compared to many other cultural topics. Then, the community members themselves lack asufficient and conscious perception of the true essence of architecture and construction, and their diverse applications in many fields, and in the major of housing inparticular. Whereas the concept of housing, which stands as the most fundamental component of architecture and construction, is far more important and inclusive than thecontent broadcasted by the mass media, and widely known among the masses. Where the mass media vision of architecture and construction is limited to the notion th athousing projects are merely architectural designs imbedded within investment enterprises, that target profit at the first place, and that such projects are no longer inconsistent compliance with the basic needs of the units users, in terms of: functional spaces, the social or environmental needs, in accordance with the community's cultureand its distinctive characteristics.Consequently, this research sheds light on the influence exercised by the mass media on the society's culture, consciousness, awareness, and perception of the essence ofarchitecture and settlement. In addition to the impacts of the culture instilled by the mass media on architecture, construction, and the built environment in general, andhousing in particular, in order to establish interactive positive relationships between the mass media and the society's understating / perception of architecture andconstruction in general, and housing in particular.This research mainly aims at: raising the society members' awareness and perception of the concepts and basics of architecture and construction in general, and housing inparticular; heighten the awareness of the society members seeking housing about architecture, construction, and settlement gradually, through the different sources of massmedia, which shall contribute to the maximization of such member's ability to choose properly, and meet his/her basic needs. The objectives of the research can be summedup as follows:- Demonstrating how mass media can affect the definition of the essence and concepts of architecture and construction in general, and housing in particular.- Evaluating the role played by mass media, in terms of positivity and negativity, through running an analysis of the messages conveyed by media and advertising, whichare often influenced by the vision of the investing developers, in quest for marketing their housing products.- Detecting the criteria upon which the mass media rely in order to market an architectural product, to see if such mass media adopt honesty in presenting the characteristicsof the product, and to see whether such presentation provides the user with the informed knowledge of what he/she is going to possess or not.- Outline controls system to regulate the methods of promotion and marketing, in connection with the information to be provided by the mass media about the architecturalproducts available at the housing market, to enable residence seekers to select the most suitable product, among the available residential models, in accordance wi th theirdiverse and versatile characteristics and needs.